Predictors of Complications at Common Femoral Artery Access Site among Patients on Oral Anticoagulants and Undergoing a Cardiac Catheterization - Noor Faraz, Yasir Arfat, Imran Ellahi Soomroo, Sarfraz Ali Mangi, Afzal Qasim, Masroor Hussain Sharfi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: It is not clear whether patients receiving oral anticoagulants (OC) during surgery involving access to the common femoral artery would experience more adverse effects than those not receiving OC. In this analysis, we determine whether patients receiving oral anticoagulants undergoing cardiac catheterization are at high risk of complications related to femoral site than subjects not receiving OACs. Study Settings: This study was held in the Cardiology department of Qazi Hussain Ahmed Medical Complex, Nowshera and Peoples University of Medical and Health Sciences for Women PUMHSW (SBA) Nawabshah for one-year duration from January 2021 to December 2021. Methods: A total of 300 patients were selected for the study. We regularly reviewed data from patients undergoing cardiac surgery at the same tertiary care center. A patient was classified as fully or partially anti-coagulated (Group A) if his international normalized ratio (INR) was greater than 1.6 on the surgery day or if he received new OAC or warfarin within 48 hours or less after surgery. The group without anticoagulants (Group B) had an INR of 1.6 or had stopped the new OAC and warfarin more than 48 and 24 hours prior to surgery, respectively. Results: A total of 300 patients (mean age 65.6±12.2, 60% male) were registered in the study. 20 (6.7%) were in Group A and Group B included 280(93.3%) patients. The intervention was done among 162/300 (54%) patients and received treatment with Intra-procedural anticoagulation with heparin (50.0%), bivalirudin (23.3%) or both (3.3%). GpIIb/IIIa inhibitors were used infrequently (1%). Conclusions: Compared to patients who did not receive anticoagulants during the procedure, OAC patients experienced no major serious adverse events after 30 days. Keywords: Oral anticoagulant, Common femoral artery, complications, access site.